Angiogenesis in hereditary hemorrhagic telangiectasia: VEGF165 plasma concentration in correlation to the VEGF expression and microvessel density - Sadick, Haneen; Naim, Ramin; Gößler, Ulrich; Hörmann, Karl; Riedel, Frank (International journal of molecular medicine, 2005)
Angiogenesis defines the physiologic process of capillary blood vessel formation. It is a multistep process, which is controlled by a large number of pro- and anti-angiogenic factors. Vascular endothelial growth factors (VEGF) are the best characterized pro-angiogenic factors, which play a key role in angiogenesis. Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant, multi-systemic disorder of angiogenesis, clinically characterized by severe and recurrent hemorrhages. We assume in HHT patients with increased VEGF plasma levels a high VEGF expression also correlates with the degree of microvesssel density (MVD). In 41 HHT patients and 47 healthy patients, the VEGF165 plasma concentration was determined by standard ELISA technique. Cryostat sections of 13 HHT patients were immunostained for VEGF and endothelial cells by an anti-vWF monoclonal antibody using a standard streptavidinbiotin complex procedure. The degree of vessel density was quantified by light microscopy (x200) within ‘hot spot’ areas of the HHT-tissue. All HHT cryostat sections showed a medium to strong staining for VEFG compared to healthy control tissue. The VEGF expression correlated with the VEGF165 plasma concentration and the mean MVD in HHT patients. HHT patients with medium VEGF staining revealed significantly lower VEGF165 plasma concentrations and a lower mean MVD (204±12 vessels/per microscopic field) than HHT patients with strong VEGF staining (327±76 vessels/per microscopic field). High VEGF expression in patients with HHT in correlation to their VEGF165 plasma levels and the microvessel density may support the theory that VEGF functions as an important regulator and key protein of angiogenesis, even in HHT.